2022
DOI: 10.1039/d2ob00637e
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical 5-exo-dig aza-cyclization of 2-alkynylbenzamides toward 3-hydroxyisoindolinone derivatives

Abstract: Preparation of the biologically relevant 3-hydroxyisoindolinones from the readily available 2-alkynylbenzamides is an appealing synthetic approach. However, such kind of compounds preferably undergoes O-attacked 5-exo-dig/6-endo-dig cyclizations. Herein, we report the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…From the above observations and earlier literature reports, 14 we propose the plausible mechanism as shown in Scheme 3. Initially, substrate 1 undergoes the proton coupled electron transfer (PCET) process to generate the amidyl radical B in the presence of a base via single electron transfer (SET) at the anode.…”
supporting
confidence: 67%
“…From the above observations and earlier literature reports, 14 we propose the plausible mechanism as shown in Scheme 3. Initially, substrate 1 undergoes the proton coupled electron transfer (PCET) process to generate the amidyl radical B in the presence of a base via single electron transfer (SET) at the anode.…”
supporting
confidence: 67%
“…The attachment of an o -alkyne 14 shifts the reactivity from the above migratory cyclization to a straightforward aza-cyclization. 15 Indeed, we found that linking the aryl acetylene to the ortho -position of the benzenesulfonamide results in the anticipated cascade ortho -cyclization ( Scheme 1C ). 16 More interestingly, the extra incorporation of the 2-methyl substitution favors migratory cyclization.…”
mentioning
confidence: 95%
“…13 In our previous research, we found that the electrochemically generated amidyl radical of 2-alkynylbenzamide underwent 5-exo-dig radical aza-cyclization to afford diverse 3-hydroxyisoindolinone. 14 We envisaged that the use of Et 3 N•3HF as the supporting electrolyte should also facilitate the generation of the same amidyl radical. While Et 3 N•3HF also serves as the nucleophilic fluorinating agent, 15 the corresponding fluorinated isoindolin-1-one derivatives should be readily obtained.…”
mentioning
confidence: 99%
“…Specifically, the electrochemical synthesis of heterocyclic compounds via the electrochemically generated N-centered radicals has been widely reported . In our previous research, we found that the electrochemically generated amidyl radical of 2-alkynylbenzamide underwent 5 -exo-dig radical aza-cyclization to afford diverse 3-hydroxyisoindolinone . We envisaged that the use of Et 3 N·3HF as the supporting electrolyte should also facilitate the generation of the same amidyl radical.…”
mentioning
confidence: 99%